Crossroads: Performance Studies and Irish Culture - Brady, Sara. author. aut Link
XIV, 255 p. 9 illus.
Keywords: The highly performative categories of 'Irish culture' and 'Irishness' are in need of critical address, prompted by recent changes in Irish society, the arts industry and modes of critical inquiry. This book broaches this task by considering Irish expressive culture through some of the paradigms and vocabularies offered by performance studies.